AN Evaluation of a Discipleship Process Addressing Christians' Inner Life Issues - Lang, James A. (Christian education journal, 2015)
Many Christians face blockages in their quest for spiritual maturity that retard that process. These can be spiritual, emotional, and/or psychological in nature. This article reports on a mixed-methods research study evaluating the effectiveness of the transformational learning resulting from a discipleship process called the Immersion Experience by Aphesis Group Ministries. This ministry and process seek to take the Gospel of Jesus Christ to the innermost parts of the human heart. The theoretical framework of this study was drawn from Mezirow's Transformative Learning Theory, Argyris and Schon's double-loop learning, and Kegan and Lahey's Immunity to Change.